Characterization of β-glucosidases from Meridianimaribacter sp. CL38: Characterization of β-glucosidases from Meridianimaribacter sp. CL38 - Hong , Clarine Wan Ling; Chen, Sye Jinn; Liew, Kok Jun; Lam, Ming Quan; Zakaria, Muhammad Ramziuddin; Chong, Kheng Loong; Chong, Chun Shiong (Journal of Tropical Life Science, 2023)
The production of second-generation biofuel requires a huge amount of freshwater. It is estimated that at least three gal of freshwater is used to produce one gal of biofuel. The replacement of freshwater with seawater serves as a potential alternative in biofuel generation. Therefore, salt-tolerant enzymes play an important role in saccharification and fermentation process. Halophilic β-glucosidase is one of the key enzymes for the process. In this study, the β-glucosidase of halophile Meridianimaribacter sp. CL38 isolated from mangrove soil was characterized. Strain CL38 achieved maximum production of β-glucosidase at 12th hour of growth. The β-glucosidase showed highest activity at 2% (w/v) NaCl while highly stable at salt concentration ranging from 1-2% (w/v) (more than 96% of relative activity). Its β-glucosidase activity remained active in the presence of 5mM Mn2+, Mg2+, Ca2+ ions, and 1% (v/v) Tween-20 and Tween-80. The draft genome sequence of strain CL38 was retrieved from GenBank database and submitted to dbCAN meta server for CAZymes annotation. Strain CL38 harbors 44 GHs and GH3 are annotated as β-glucosidases. The β-glucosidases of Meridianimaribacter flavus (99.61%) and Mesoflavibacter sabulilitoris (97.44%) showed the closest identity with Bgl3a and Bgl3b protein sequences from strain CL38, respectively. Glycoside hydrolase family 3 domain was identified in both enzymes via InterPro scan server. The presence of signal peptides indicated that both enzymes were secreted extracellularly. Five motifs were identified in Bgl3a and Bgl3b, with the active site (nucleophile) found at Asp296 and Asp297, respectively. Collectively, these β-glucosidases could be potentially used in the biofuel production, in particular the lignocellulosic biomass pretreatment process. This is the first attempt to characterize the β-glucosidase in genus Meridianimaribacter as so far none of the lignocellulolytic enzymes from this genus were characterized.